English Learning Achievement of Prathom Suksa 2 Students with Active Learning Activities - Srilapho, Tharathep; Robroo, Intira (Journal of Humanities and Social Sciences, Rajapruk University, 2023)
The objectives of this research were 1) to compare students’ English achievement between the treatment group taught with the active learning activity and the control group taught with the traditional approach, and 2) to study students’ attitudes after learning activities based on active learning. The participants were Pratomsuksa 2 students of Anubansrithat School, Udon Thani province in the second semester of 2020. They were selected purposively and with cluster sampling. The study was divided into the treatment group and the control group, each group has 28 students. The research instruments were lesson plans, the English achievement test, and students' attitudes towards active learning activity assessment form. Data were analyzed by using mean, standard deviation, and t-test. The research findings were 1) the English achievement of the treatment group taught with the active learning activity was higher than the control group taught with the traditional approach at a .05 level, and 2) the students’ attitudes after learning with active learning activities overall were at the highest level with a mean was 4.48 and a standard deviation was 0.60.